Development Of Marine Tourism Potential In East Likupang Waters, North Minahasa District - Maryen, Yakob Oskar; Manembu, Indri Shelovita; Ngangi, Edwin L. A.; Roeroe, Kakaskasen Andreas; Sambali, Hariyani; Darwasito, Suria; Sumilat, Deiske Adeliene (Jurnal Ilmiah Platax, 2024)
This research aims to determine the potential for marine tourism in East Likupang Waters, determine the suitability of developing marine tourism in East Likupang Waters, and recommend marine tourism management, collecting primary data through observation and in-depth interviews directly with the community. Secondary data through studies of research results, scientific publications, the Minahasa Regency Maritime and Fisheries Service, and the North Minahasa Regency Maritime and Fisheries Service. Biophysical data is as follows. Observation of coral conditions using Line Intercept Transect (LIT). b) Observation of fish using Underwater Fish Visual Census (UVC). Water quality using a water quality checker (Horiba brand). Apart from that, data analysis uses a matrix of suitability for marine tourism areas, and beach tourism and provides weighting. The results of this research show that the potential that exists in East Likupang Waters and its surroundings includes physical and non-physical potential that has the potential and can be developed into a marine tourism attraction. Carrying capacity and beach recreation Surabaya Beach beach area 2000 (m²) 533 people/day Pulisan Beach 2000 (m²) 533 people/day c) Paal Beach 1000 (m²) 267 people/day Kalinaun Beach 3000 (m²) 800 people/day, It was found that the percentage of coral cover in East Likupang Waters was 47.04%, with a marine tourism suitability index value of 62, which means that the suitability of the East Likupang Waters marine tourism area is included in the conditionally appropriate criteria. Keywords: Potential, Marin Tourism, East Likupang Waters Abstrak Penelitian ini bertujuan untuk mengetahui potensi wisata bahari di Perairan Likupang Timur, mengetahui kesesuaian pengembangan wisata bahari di Perairan Likupan Timur dan merekomendasikan pengelolaan wisata bahari, pengumpulan data primer melalui observasi dan wawancara mendalam langsung kepada masyarakat. Data sekunder melalui kajian hasil penelitian, publikasi ilmiah, Dinas Kelautan dan Perikanan Kabupaten Minahasa, dan Dinas Kelautan dan Perikanan Kabupaten Minahasa Utara. Data biofisik adalah sebagai berikut. Pengamatan kondisi karang menggunakan Line Intercept Transect (LIT). b) Pengamatan ikan menggunakan Underwater Fish Visual Census (UVC). Kualitas air menggunakan alat pemeriksa kualitas air (merek Horiba). Selain itu analisis data menggunakan matriks kesesuaian kawasan wisata bahari, dan wisata pantai serta memberikan pembobotan. Hasil penelitian menunjukkan bahwa potensi yang ada di Perairan Likupang Timur dan sekitarnya meliputi potensi fisik dan non fisik yang mempunyai potensi dan dapat dikembangkan menjadi daya tarik wisata bahari. Daya dukung dan rekreasi pantai Pantai Surabaya Luas pantai 2000 (m²) 533 orang/hari Pantai Pulisan 2000 (m²) 533 orang/hari c) Pantai Paal 1000 (m²) 267 orang/hari Pantai Kalinaun 3000 (m²) 800 orang/hari, Diketahui persentase tutupan karang di Perairan Likupang Timur sebesar 47,04% dengan nilai indeks kesesuaian wisata bahari sebesar 62 yang berarti kesesuaian kawasan wisata bahari Perairan Likupang Timur termasuk dalam kriteria layak bersyarat. Kata Kunci: Potensi; wisata bahari; Perairan Likupang Timur.